Creative personality and its dignicular role in the formation of a known economy in the conditions of the challenges of globalization of informational society - Kiurchev, Volodymyr; Кюрчев, Володимир Миколайович; Кюрчев, Владимир Николаевич; Oleksenko, Roman; Олексенко, Роман Іванович; Олексенко, Роман Иванович (My University, 2019)
EN: The urgency of the research is that the conditions for the formation of a creative personality, which are the result of the formation of a creative and knowledge economy, in which the given type of personality is in demand, is presented. Problem statement – the phenomenon of a creative personality as a phenomenon and a basis for formation of a creative and knowledge economy in the conditions of globalization challenges and trends 4.0. It is the information society and social entrepreneurship that are the main factors in the formation and development of a creative and knowledge economy, which requires the formation of a creative personality. UK: Актуальність дослідження в тому, що представлено умови формування креативної особистості, що є результатом формування креативно-знаннєвої економіки, в якій витребуваною є даний тип особистості. Постановка завдання – феномен креативної особистості як феномен і основа для формування креативно-знаннєвої економіки в умовах викликів та трендів глобалізації 4.0. Саме інформаційне суспільство та соціальне підприємництво виступають головними чинниками становлення і розвитку креативно-знаннєвої економіки, яка вимагає формування креативної особистості. RU: Актуальность исследования в том, что представленые условия формирования креативной личности, являются результатом формирования креативно-знаниевой экономики, в которой нуждается данный тип личности. Постановка задачи - феномен креативной личности как феномен и основа для формирования креативно-знаниевой экономики в условиях вызовов и трендов глобализации 4.0. Именно информационное общество и социальное предпринимательство выступают главными факторами становления и развития креативно-знаниевой экономики, требующей формирования креативной личности.
Креативна особистість та її визначальна роль у формуванні економіки знань в умовах викликів глобалізації інформаційного суспільства
Креативная личность и ее определяющая роль в формировании экономики знаний в условиях вызовов глобализации информационного общества
Keywords: informational and knowledge society; creative personality; creativity; creative and value orientations; creative and knowledge economy; creative and knowledge education; інформаційно-знаннєве суспільство; креативна особистість; творчість; креативно-ціннісні орієнтації; креативно-знаннєва економіка; креативно-знаннєва освіта; информационно-знаниевое общество; креативная личность; творчество; креативно-ценностные ориентации; креативно-знаниевая экономика; креативно-знаниевое образование